2012
DOI: 10.1002/jcp.22958
|View full text |Cite
|
Sign up to set email alerts
|

AMIGO is expressed in multiple brain cell types and may regulate dendritic growth and neuronal survival

Abstract: Amphoterin-induced gene and ORF (AMIGO) is a brain-enriched transmembrane immunoglobulin (Ig) superfamily protein with six extracellular leucine-rich repeats (LRR) and a single immunoglobulin-like (Ig) domain. We report here that AMIGO is a glycosylated protein widely expressed in the central nervous system (CNS), and can be found in neurons, astrocytes as well as oligodendrocytes. In morphologically mature primary neurons, endogenous AMIGO, and transfected full length AMIGO (AMIGO-FL) are largely dendritic, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…In 5-dpf zebrafish larvae, Amigo1 expression is found in most brain areas that already have functionally active neural circuits. This finding also resembles the situation in rodents, in which AMIGO1 expression is increased in postnatal brain during construction of the adult-type circuitry and is found in practically all areas of the CNS in most neurons and their fibers in young adults (4,7,9). Such a conserved spatiotemporal expression pattern in vertebrates suggests a conserved function in the CNS development.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In 5-dpf zebrafish larvae, Amigo1 expression is found in most brain areas that already have functionally active neural circuits. This finding also resembles the situation in rodents, in which AMIGO1 expression is increased in postnatal brain during construction of the adult-type circuitry and is found in practically all areas of the CNS in most neurons and their fibers in young adults (4,7,9). Such a conserved spatiotemporal expression pattern in vertebrates suggests a conserved function in the CNS development.…”
Section: Discussionsupporting
confidence: 78%
“…The crystal structure of the AMIGO1 dimer has recently revealed that homophilic binding of AMIGO1 occurs through its LRR domains (8). In addition, AMIGO1 and AMIGO2 (also designated as Alivin1) have been reported to enhance survival of neurons in culture (9,10). Furthermore, AMIGO1 has recently been found to bind to the Kv2.1 potassium channel and to affect excitability of central neurons via the Kv2.1 interactions (11).…”
mentioning
confidence: 99%
“…Recent studies provide compelling evidence that transmembrane proteins containing extracellular leucine-rich repeat (LRR) domains control neuronal connectivity functioning as regulators of axon guidance, dendritic growth, synapse formation, and plasticity [15][16][17]. Distinct LRR protein families are highly enriched in the CNS, especially in the hippocampus, where they play a critical role in organizing synaptic connections into functional neural circuits.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently it has been reported that AMIGO1 is also expressed in astroglia and oligodendroglia and that the protein in neurons localizes mainly to dendrites but not axons. Interestingly, an AMIGO1 mutant lacking the LRR domain is mis-allocated to axons rather than dendrites and is transported to the cell surface faster than wild-type AMIGO1 or an AMIGO1 mutant lacking the Ig module (see below) (Chen et al 2012 ).…”
Section: Expressionmentioning
confidence: 99%
“…They are composed of a ~400 amino acids long ectodomain consisting of six N-terminal LRRs with NF and CF domains, and a membrane-proximal Ig module, a transmembrane domain, and a ~100 amino acids long short cytoplasmic domain (Kuja-Panula et al 2003 ;Ono et al 2003 ;Chen et al 2012 ). The ectodomain of AMIGO1 contains fi ve sites for N-linked glycosylation: two in the LRR domain and three in the Ig module.…”
Section: Genes and Proteinsmentioning
confidence: 99%